Branched-chain amino acid catabolism promotes M2 macrophage polarization - Lu, Manxi; Luo, Da; Zhang, Zixuan; Ouyang, Feng; Shi, Yihong; Hu, Changyong; Su, Hang; Li, Yining; Zhang, Jiayi; Gui, Qian; Yang, Tian-Shu (Frontiers in Immunology, 2024)
IntroductionDuring an immune response, macrophages undergo systematic metabolic rewiring tailored to support their functions. Branched-chain amino acid (BCAA) metabolism has been reported to modulate macrophage function; however, its role in macrophage alternative activation remain unclear. We aimed to investigate the role of BCAA metabolism in macrophage alternative activation.MethodThe metabolomics of BMDM-derived M0 and M2 macrophages were analyzed using LC-MS. BCAAs were supplemented and genes involved in BCAA catabolism were inhibited during M2 macrophage polarization. The expression of M2 marker genes was assessed through RT-qPCR, immunofluorescence, and flow cytometry.Results and discussionMetabolomic analysis identified increased BCAA metabolism as one of the most significantly rewired pathways upon alternative activation. M2 macrophages had significantly lower BCAA levels compared to controls. BCAA supplementation promoted M2 macrophage polarization both in vitro and in vivo and increased oxidative phosphorylation in M2 macrophages. Blocking BCAA entry into mitochondria by knockdown of SLC25A44 inhibited M2 macrophage polarization. Furthermore, M2 macrophages polarization was suppressed by knockdown of Branched-chain amino-acid transaminase 2 (BCAT2) and branched chain keto acid dehydrogenase E1 subunit alpha (BCKDHA), both of which are key enzymes involved in BCAA oxidation. Overall, our findings suggest that BCAA catabolism plays an important role in polarization toward M2 macrophages.